Homotopy perturbation method for solving perturbation problems - Chowdhury, Md. Sazzad Hossien (2014)
In this paper, the application of homotopy perturbation method (HPM) is extended to the perturbation problems. The HPM yields an analytical solution in terms of a rapidly convergent infinite power series with easily computable terms. The efficiency of the HPM is examined by several illustrative examples. Comparisons with the solutions obtained by the Adomian decomposition method (ADM) show the efficiency of HPM in solving perturbation problems.